Addition of vegetable oil to enhance the biosynthesis of butenyl-spinosyn in a high production strain Saccharopolyspora pogona - Zhouqin Xu; Xinying Li; Chao Guo; Chang Su; Chao Wang (PLoS ONE, 2025)
Butenyl-spinosyn discovered from Saccharopolyspora pogona, is a broad-spectrum bioinsecticide. In order to further improve the production, the fermentation medium of a high-production strain Sa. pogona ASAGF30A11 obtained by mutagenesis, was optimized by adding different species and concentrations vegetable oil. In our study, the effect of peanut oil on the growth and production was proved by monitoring the growth curves, key gene transcription level and content of acyl-CoA. After adding 10 g/L of peanut oil, the additional carbon sources redirected the carbon flux toward strain growth, inhibiting the synthesis of butenyl-spinosyn, while increasing biomass by approximately 1.5-fold. However, when adding 1 g/L of peanut oil, it functions as a surfactant, greatly promoting the synthesis of butenyl-spinosyn, resulting in a 1.52-fold increase in production. The research provides a promising strategy to improve butenyl-spinosyn production.